Can Drug-Induced Yawning Serve as a Biomarker for Drug Safety and Effectiveness? - Mohammad Rokan Ali; Khaled Alzaeem; Mostafa Bejermie; Cole Ngwachi Mangong Fofang; Siamand Mohamad; Parisa Gazerani (Future Pharmacology)
Background/Objectives: Yawning, a common physiological behavior, has emerged as a potential biomarker for drug responsiveness and side effects. This scoping review synthesizes current evidence on drug-induced yawning (DIY), focusing on its neurobiological mechanisms and clinical implications. Methods: A scoping review (INPLASY registration number: INPLASY202540048) was conducted using PubMed, Scopus, and Web of Science, including studies published in the past decade. The review adhered to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and Cochrane Handbook guidelines, ensuring systematic selection. Selected articles led to the analysis of 10 relevant studies encompassing 473 participants. Studies were evaluated for relevance to DIY, neurobiology, and clinical applications, with thematic analysis used to synthesize findings. Results: Four key themes emerged. (1) Yawning patterns: DIY involves frequent episodes (up to 80 yawns/day), varying by drug type and dosage. (2) Neurobiological mechanisms: Yawning is mediated by serotonin, dopamine, and oxytocin pathways, particularly via 5-HT2C and μ-opioid receptors. (3) Drug responsiveness: DIY is linked to SSRIs, opioids, and dopamine agonists. SSRIs induce yawning, while opioids suppress it, reflecting distinct neurochemical effects. (4) Clinical implications: Yawning may serve as a non-invasive biomarker for drug efficacy and side effects, particularly in opioid withdrawal and SSRI monitoring. Conclusions: DIY holds promise as a biomarker for drug safety and effectiveness, but research is limited by small sample sizes, methodological variability, and the absence of standardized yawning metrics. Future studies should establish consistent measures, account for interindividual variability, and evaluate DIY’s long-term clinical utility across diverse populations.